Experimental Studies of Twist Ratio Effect to The Heat Transfer Enhancement Using Square Cut Tape and Classical Tape Insert - Alfan Adha Hutama Putra; Agung Tri Wijayanta; Indri Yaningsih (Mekanika: Majalah Ilmiah Mekanika, 2017)
EXPERIMENTAL STUDIES OF TWIST RATIO EFFECT TO THE HEAT TRANSFER ENHANCEMENT USING SQUARE CUT TAPE AND CLASSICAL TAPE INSERT